Vibratory motion of fourth order fluid film over a unsteady heated flat - Mustafa, Mamat; Muhammad Ismail, Mohmand; Qayyum, Shah; Taza, Gul (2017)
Analysis of heat transfer is studied in magnetohydrodynamic (MHD) thin layer flow of an unsteady fourth grade fluid past a moving and oscillating vertical plate for lift and drainage problem. The governing equations are modelled in terms of nonlinear partial differential equations with some physical boundary conditions. Two different analytical methods, namely Adomian Decomposition Method (ADM) and the Optimal Homotopy Asymptotic Method (OHAM) are used for finding the series solution of the problem. The solutions obtained through two different techniques are compared using graphs and tables and found an excellent agreement. The variants of embedded flow parameters in the solution are analyzed through graphical illustrations.